Um artista na escola e uma visita ao parque: Experiências em educação e arte por meio do desenho. - Silva, Núbia de Souza (2023)
This research quantitatively contributes to quality teaching since it offers systematized knowledge that is consistent with public education policy, based on the assertion that the teaching of Art serves as an auxiliary instrument in the formation of people aware of their duty and right in society, through of the qualitative methodology, a mediator that encourages the student to build theoretical and practical knowledge about artistic production. The perspective of dynamics in the classroom in order to sharpen the artistic side of the student as well as to promote the decoloniality of thoughts and ideas was achieved by putting into practice the project artists at school, with the participation of the plastic artist Sinval. The effect observed after close contact between students and artist was significant in terms of individualized creativity based on experiences and feelings, with drawing being the main tool for learning and expression. The discipline of art at school is not only intended to entertain or relax students, but rather as a tool for solving abstract mathematical problems, for botanical records, in cartographic constructions, even if technological advances have modernized such contents. From this fact, it emerges that educating is a holistic and complex action, which happens from the inside out, that is, from the student's perception of everything around him. Therefore, the educational action is present in all spaces and at all times.